Safety and short-term outcomes of laparoscopic surgery for advanced gastric cancer after neoadjuvant immunotherapy: A retrospective cohort study - Su, Jin; Guo, Weihong; Chen, Zhian; Wang, Lingzhi; Liu, Hao; Zhao, Liying; Lin, Tian; Li, Fengping; Mao, Xinyuan; Huang, Huilin; Yu, Jiang; Li, Guoxin; et al. (Frontiers in Immunology, 2022)
Background: Immune checkpoint inhibitors (ICIs) have been increasingly used for the treatment of advanced gastric cancer (AGC). However, it is unknown concerning the safety and the short-term outcomes of laparoscopic gastrectomy for patients with AGC after neoadjuvant immunotherapy (NAI). Methods: We retrospectively analyzed the patients with AGC who underwent laparoscopic surgery after neoadjuvant therapy between January 1, 2019 and October 31, 2021. We further compared the differences of postoperative complications, overall response rate, adverse events, surgical parameters, and postoperative recovery between the two cohorts of NAI group (NAI plus chemotherapy) and neoadjuvant chemotherapy (NAC) group. Multivariable regression analyses were used to determine the risk factors for the overall response rate. Results: Overall, 80 patients were enrolled, of which 30 cases were included in the NAI cohort and 50 in the NAC cohort. The overall rate of postoperative complications was 30.0% in both groups (P = 1.000). The overall response rate was 70.0% in the NAI cohort and 40% in the NAC cohort (P = 0.012). The adverse effects were found in 16 cases (53.3%) of the NAI cohort and 23 cases (46.0%) of the NAC cohort (P = 0.645). There was no statistical difference in intraoperative bleeding (50 vs 50 ml, P = 0.983), operation time (320.9 min vs 303.5 min, P = 0.382), dissected lymph node count (43.5 vs 40.0, P = 0.364), first postoperative anal aerofluxus (3 days vs 3 days, P = 0.091), first liquid diet (4 days vs 5 days, P = 0.213), and postoperative length of stay in the hospital (8 days vs 7 days, P = 0.508) between the two groups. NAI was estimated to be the independent protective factor [odds ratio (OR) 4.931, 95% confidence interval (CI) (1.385-17.559), P = 0.014] for odds to overall response rate, whereas vessel invasion was found to be the significant risk factor [OR 0.113, 95% CI (0.027-0.475), P = 0.003]. Conclusions: Laparoscopic surgery after NAI combined with chemotherapy is a safe therapeutic choice for AGC and may bring better short-term outcomes due to a higher overall response rate.